Diabetic Foot Classification (Wagner Classification System) as A Predictor of Outcome: Study of 50 Patients - EHSAN UR REHMAN, ZAFAR IQBAL GONDAL GHUL, NOSHAD AKBER, ZIAULLAH MALIK (Journal of Fatima Jinnah Medical University, 2018)
Objective: To predict the outcome of diabetic foot wound using Wagner classification system. Design: Descriptive Study Setting: Surgical Unit 1, Department of Surgery, Jinnah Hospital Lahore Duration of Study: One year (January 2010 to December 2010) Subject & Method: Fifty cases were included in this study. In all the patients wounds were graded using Wagner classification system, Ulcer was labeled infected if a purulent discharge was present along with the other local signs (warmth, erythema, pain, oedema and lymphadenopathy). Main Outcome Measures: Grades according to Wagner classification system Condition of ulcers Amputation done. Results: Out of these 50 patients 30 (60%) were males and 20 (40%) were females (Table-1). The mean age of male patients was 54.33+8.04 and female patients 56.40+6.52. Out of total 50 patients, 24 patients (48%) were graded as Grade-I according to Wagner classification system. 13 patients (26%) were labeled as Grade-II, 9 patients (18%) had a presentation of Grade III of classification system and 4 patients (8%) were put in category of Grade-IV whereas there was no presentation in Grade-V and Grade-0 at all. At the end of one year time, out of 24 patients (48%) who were labeled as Grade-I, only one patient underwent amputation and percentage number amputation was (4.2%), and among the remaining 23 patients percentage number of healed ulcers was 87% against the percentage number of unhealed ulcers as 13%. Similarly, in the 13 patients (26%) with diabetic foot ulcer of Grade-II variety, the percentage number of amputation was 15.4% (2 patients) whereas in remaining 11 patients (22%) percentage number of healed ulcers was (45.5%) against percentage number of unhealed ulcers which was (54.5%). Likewise out of the 9 patients (18%) which were put in Grade-III 8 patients underwent some kind of amputation and the percentage number of amputation was found to be (88.9%) , while the remaining 1 patient in this group showed complete healing with a percentage number of healed ulcer as 100% interestingly. All patients who were labeled as Grade-IV i.e. 4 (8%) underwent some form of amputation with percentage number amputation as 100%. Conclusion: The results of this study indicate that outcomes deteriorate with increasing grade of Wangner classification system. As in this study, we have shown a trend towards an increased prevalence of amputation with advancing depth and presence of infection.